2015
DOI: 10.1523/jneurosci.4962-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Olig1 Function Is Required for Oligodendrocyte Differentiation in the Mouse Brain

Abstract: Oligodendrocyte differentiation and myelination are tightly regulated processes orchestrated by a complex transcriptional network. Two bHLH transcription factors in this network, Olig1 and Olig2, are expressed exclusively by oligodendrocytes after late embryonic development. Although the role of Olig2 in the lineage is well established, the role of Olig1 is still unclear. The current studies analyzed the function of Olig1 in oligodendrocyte differentiation and developmental myelination in brain. Both oligodend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 45 publications
4
71
0
1
Order By: Relevance
“…4). Collectively these sequence motifs preferentially bind to ten transcription factors, many of which have links to stress-related behaviors and disorders, such as Tcf3 , Gmeb2 , and Olig1 (see Discussion) 5456 . Subsequent examination of the sequence data for each DhMR residing in the acute stress-related differentially expressed genes revealed that all candidate functional DhMRs contained at least one of the enriched transcription factor binding sequence motifs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Collectively these sequence motifs preferentially bind to ten transcription factors, many of which have links to stress-related behaviors and disorders, such as Tcf3 , Gmeb2 , and Olig1 (see Discussion) 5456 . Subsequent examination of the sequence data for each DhMR residing in the acute stress-related differentially expressed genes revealed that all candidate functional DhMRs contained at least one of the enriched transcription factor binding sequence motifs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Olig2 can interact with transcriptional co-regulators Nkx2.2 or Zfp448 to further promote OPC differentiation in ovo (Wang et al, 2006; Zhou et al, 2001). The initial analysis of the function of Olig1, a close homolog of Olig2, indicates a developmental delay in OL differentiation in the spinal cord of an Olig1 -null mouse strain (Lu et al, 2002), while a recent study of the mutant line indicates persistent impairment of OPC commitment and OL differentiation in the corpus callosum from early postnatal stages to adulthood (Dai et al, 2015). This observation indicates a primary role of Olig1 in OL development and subsequent myelination in brain, but not spinal cord, suggesting a region-specific Olig1 function OL development in the CNS.…”
Section: Control Of Opc Specification and Plasticity By Intrinsic Facmentioning
confidence: 99%
“…Overall, these results demonstrated that VPA induced several morphological variations, as previously described in other tumors (45): we speculated that the HDAC inhibitory action of VPA could trigger reactivation of genes involved in differentiation, usually silenced in cancer stem cells (12,13). In fact, for example, after 30 days of treatment, we identified a potentially reactivating methylation change of OLIG1 and OLIG3 promoters, which are involved in oligodendrocyte and neuronal differentiation (46,47), from the methylated to the unmethylated status in G144 and GBM2 cells, respectively (Table III).…”
Section: Discussionmentioning
confidence: 99%